Variation of elective healthcare in West Africa: secondary analysis of an inguinal hernia international cohort study - Maria Picciochi; Anita Eseenam Agbeko; Fareeda Agyei; Toni Risteski; NIHR Global Health Research Unit on Global Surgery (Impact Health, 2024)
Introduction: Access and quality of elective healthcare varies globally as shown in a previous study where inguinal hernia was used as a tracer condition. Inguinal hernia incidence increased from 1990 to 2019 but access to its repair is not fully characterised. The aim of this study was to evaluate access and quality of elective healthcare in West Africa comparing it with the other regions. Methods: We conducted a secondary analysis of a prospective, cohort, international study of hernia surgery. Data was collected from all consecutive patients undergoing primary inguinal hernia repair between 30 January and 21 May 2023. Inguinal hernia was chosen as the tracer condition to evaluate elective healthcare. In this analysis, we characterised the group of patients undergoing inguinal hernia repair in West Africa, comparing adults and children. We compared the access and quality metrics in West Africa with those measured and reported globally. Results: We included 18,058 patients undergoing inguinal hernia repair globally, from which 1,079 patients were from West Africa. Most included patients were adults (76.7%, 828/1,079) without comorbidities. Emergency surgery and bowel resection adjusted rates were higher in West Africa than globally (18,0% and 4.0% vs 7.9% and 1.5%, respectively). Waiting time for elective surgery was longer in West Africa (median 10.3 vs 8.0 months). Out-of-pocket payment was the most common financing method in West Africa patients (54.5%, 588/1079). Mesh adoption was less than half compared to the other regions globally (44.9% vs 94.8%). Postoperative complications were lower than other regions (adjusted rate 10.8% vs 13.3%). Discussion: This study identified that access to elective healthcare in West Africa still needs to be improved despite previous actions to tackle this. Adult, inguinal hernia patients would benefit if mesh was used to avoid recurrence in future. Reducing out-of-pocket payments might be essential to address both problems.
Keywords: inguinal hernia; West African College of Surgeons; elective healthcare